Structural flexible hybrid electronics for embedded sensors and functionality - Ang, Leh Shuen (2019)
There have been many works of automated 3D hybrid manufacturing with various aspects of it to be improved on. This paper focus on the aspect of micro-dispensing and aims to develop it further by applying the automated integrated technology on the miniaturization of electronic circuits. This aim of this research is to identify factors that will help the industry consistently produce a narrow and linear conductive trace by changing the width of the trace and eliminating the gaps in traces. This research will also focus and analyse on how changes in the parameters of identified factors can affect and give different outcomes. In the experiments, the average diameter size of individual points is used to gauge the width of the trace whereas the maximum gap size is used to detect the presence of gaps in the trace. The experimental results obtained show that a higher dispensing height and lower extrusion time will produce a narrow and linear conductive trace with zero gaps. The significance of each factors on the average diameter size and maximum gap size is scientifically proven through analysis of variance. Much research is still needed to fully identify and understand the contributing variables. It is hoped that, with this research paper, researchers gain more information regarding micro-dispensing for miniaturization.